Melatonin Role in Ameliorating Radiation-induced Skin Damage: From Theory to Practice (A Review of Literature) - Abbaszadeh, A. (J Biomed Phys Eng, 2017)
Normal skin is composed of epidermis and dermis. Skin is susceptible to radiation damage because it is a continuously renewing organ containing rapidly proliferating mature cells. Radiation burn is a damage to the skin or other biological tissues caused by exposure to radiofrequency energy or ionizing radiation. Acute skin reaction is the most frequently occurring side effect of radiation therapy. Generally, any chemical/biological agent given before or at the time of irradiation to prevent or ameliorate damage to normal tissues is called a radioprotector. Melatonin is a highly lipophilic substance that easily penetrates organic membranes and therefore is able to protect important intracellular structures including mitochondria and DNA against oxidative damage directly at the sites where such a kind of damage would occur. Melatonin leads to an increase in the molecular level of some important antioxidative enzymes such as superoxide, dismotase and glutation-peroxidase, and also a reduction in synthetic activity of nitric oxide. There is a large body of evidence which proves the efficacy of Melatonin in ameliorating UV and X ray-induced skin damage. We propose that, in the future, Melatonin would improve the therapeutic ratio in radiation oncology and ameliorate skin damage more effectively when administered in optimal and non-toxic doses.